A Framework of Systematic Land Use Vulnerability Modeling Based on Seismic Microzonation : A Case Study of Miri District of Sarawak, Malaysia - Imtiyaz Akbar, Najar; Raudhah, Ahmadi; Yunika Kirana, Abdul Khalik; Nurul Zawiyah, Mohamad; Mohd Azizul Hafiz, Jamian; Nadeem Akbar, Najar (IIETA, 2022)
The objective of this research is to develop the framework for sustainable land-use planning on the basis of seismic microzonation to reduce the devastating effects of future earthquakes by utilizing the software geographical information system (ArcGIS). Miri district of Sarawak in Malaysia has been chosen as the study area because of having the highest peak ground acceleration which is 0.09g in terms of the 10% probability of exceedance in 50 years. In addition, the frequency of an earthquake with a magnitude up to 5.3 is approximately every 5-7 years. Therefore, it is vital to introduce land use planning in order to diminish the adverse effects of earthquakes in the future. For this purpose, Google Earth Pro was used for the collection of satellite image data for land use planning purposes. From the results, it was found that the seismic hazard in the Miri district varies from low to high corresponding to 2475 years of return period with low to moderate as predominant over the Miri district. Only a few areas are under high hazard. Also, the land use planning map was compared with the current land use map acquired from satellite imagery and it was found that all built-up is in the low hazard area. It is envisaged that the findings from this research will contribute immensely to the literature that will serve as background information and a guide for analysts, disaster management, engineering designers and seismologists in Malaysia and the world as a whole.